Technical Feasibility Analysis for Introduction of Ethanol Fuel in the Energy Matrix of Portugal - Gelain, Anna Júlia Lorenzzon; Emami, Seyedali (Revista de Administração da UFSM, 2014)
Greenhouse gas emissions are among the major sources of global warming issue. Carbon dioxide emitted by burning of fossil fuels has a major contribution on this effect. Renewable energy resources such as biofuels have found to be a promising alternative, with positive impacts on environment, and a significant decrease of the critical issues related to the consumption of fossil fuels. Ethanol has been used as an alternative for fossil fuels in many regions such as Brazil and USA. Despite major advantages and facilities of Ethanol, this biofuel has not yet been considered in the Portuguese energy matrix. In this paper, we present the main aspects of the life cycle of this fuel, as well as a proof of its viability through a successful case study. A Life Cycle Impact Assessment (LCIA) of wheat-based ethanol was simulated with the Gabi® software, and then crossed all the information to find out what would be the best option to introduce this biofuel in the energy matrix of Portugal. Despite the limitations on the use of this fuel (agricultural and technological factors), knowing that there are no flex vehicles in the country, recent advances in this field of research could work as a great incentive to show that it is increasingly possible to use this biofuel.